Siddha perspective of seasonal regimen (ruthu sariyai) – a review - Rakulini, R.; Sounthararajan, K. (World Journal of Pharmaceutical Research, 2020)
Introduction: Siddha Medicine is a system of traditional medicine originating in ancient Tamil Nadu in South India and Sri Lanka. Traditionally, it is taught that the siddhars laid the foundation for this system of medicine. Agastyar is considered the first Siddhar. The characteristics of people vary according to the seasonal variation (Ruthu sariyai) Therefore, it is imperative to know about Ruthu sariyai. Ancient Tamils had their own divisions of the year into different seasons (Perumpozhuthu) and of the day (Sirupozhuthu). Aim: The aim of the study is to study the siddha perspective of seasonal regimen (ruthu sariyai) in the relevant Siddha Literatures. Methodology: It is a review of relevant literatures on siddha perspective of seasonal regimen (ruthu sariyai). Data for the literature review were collected from relevant literatures. Collected data were processed and analysed. Results and Discussion: The winter season gives good health both for human beings and the plants. Early summer and the latter rainy season give moderate health, early rainy season and latter summer are the periods of diseases. The regular disciplines of food and action as mentioned for each season are followed as strictly as possible so that we could avoid the occurrences of the diseases due to the change of seasons. Conclusion: This literature review provides useful documented evidence on seasonal regimen (ruthu sariyai).
Keywords: Siddha medicine; Seasonal regimen; Ruthu sariyai; Preventive